International Capital Flows and National Creditworthiness : Do the Fundamental Things Apply As Time Goes By? - Cashin, Paul.; McDermott, C. (Washington, D.C. : International Monetary Fund, 1998)
This paper examines the optimality of international capital flows to a persistent net importer of capital, Australia, during its post-capital-controls period 1984-98. The results suggest that international capital flows were larger than optimal during the 1980s, but in the 1990s such flows have been broadly consistent with those predicted by the consumption-smoothing approach to the determination of the current account. The paper also discusses the main implications arising from measures of optimal capital flows, and compares them with the implications arising from the key concepts used in the determination of national creditworthiness.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet